MYTHOLOGICAL CRITICISM AS A LITERARY SCIENTIFIC METHOD OF ANALYSING FICTIONAL WORKS OF THE UKRAINIAN DIASPORA OF THE 20-50S OF THE XX TH C. - Sloniovska, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article examines the achievements and toolkit of the mythological school of the XIX th c., of the modern mythological criticism and neo-mythological school in implementing their toolkit for a scrupulous analysis of fictional texts of the Ukrainian diaspora’s literature in the 20-50s of the XX th c.